Conditions for effective macroprudential policy interventions. - Khan, Fahad (Economics working papers., 2017)
The dataset is used to introduce a practical way of defining effective MPP interventions on the basis of the observed stability implications in their target indicators and for analyzing macroeconomic conditions that promote effective MPP interventions. These are more likely to happen if several measures are implemented credibly and in tandem. The paper finds that monetary tightening overrides the effectiveness of MPP instruments. Output gap, credit cycle, external debt, current account, and global risk appetite also count for the likelihood of the effectiveness of MPP interventions.